Portable computer "Epson HX-20" as a data recorder computer for engineering surveying works - 172048 Abu Hamid Selamat (Sekudai : Universiti Teknologi Malaysia, 1986)
Tesis (Ijazah Sarjana Muda Ukur (Tanah)) - Universiti Teknologi Malaysia, 1986